A novel multidisciplinary paradigm for energy demand reduction in building sector: on the relationship between the energy efficiency, aesthetics and marketability of residential buildings - Aydin, Yusuf Cihat (2019)
Despite the development of energy-efficient buildings (EEBs) and more stringent building energy regulations in recent decades, the building sector’s energy demand has continued to drastically increase. This phenomenon is conceptualized in this study as the Inefficiency of Increased Building Energy Efficiency (IIBEE), which is different from Jevons paradox (the rebound effect). The phenomenon of IIBEE conceptualizes the inadequacy of existing measures to reduce the energy demand of the building sector and emphasises the necessity of developing new and more effective strategies. The phenomenon of IIBEE occurs mainly due to the lack of widespread EEB adoption as a result of market failure and applicability problems in the integrated design approach (IDA) in practice. A lack of interoperability between building stakeholders, high initial cost, unappealing aesthetic, and low market value of energy efficiency features are the fundamental reasons behind the market failure of EEBs. Aesthetic features are determined as the main driving force behind the marketability of buildings. Accordingly, increasing the number of EEBs with better marketability obtained by the enhancement of their aesthetic is introduced as a novel approach (widespread adoption approach) to reduce the energy demand of the building sector. However, applicability issues of IDA in practice and the difference of aesthetic judgement between architects and the public (buyers) are two main barriers to the aesthetic enhancement of EEBs and the applicability of the proposed widespread adoption approach. Accordingly, a novel paradigm named the Yin and Yang paradigm (YYP) was introduced to ensure the applicability of the proposed novel approach. YYP is a paradigm that offer to consider all factors involved in a decision-making process and establishing balance between them to offer multi-dimensional solution to a problem. YYP is a multidisciplinary approach that empowers individual specialists to see the perspectives of different disciplines, instead of bringing experts in different disciplines together, as in IDA. In this way, each building stakeholder can see the impact of any design changes on buildings’ different aspects simultaneously, and they can use this parametric information during their decision-making process. YYP can result in the initiation of new generation building simulation tools, effective in evaluating buildings’ different aspects simultaneously (e.g. marketability, aesthetic, energy efficiency, occupant comfort, carbon footprint and price).